The Use of Stem Cell Therapy to Reverse Opioid Tolerance. Issue 6 (29th December 2017) - Li, Fei; Liu, LiPing; Cheng, Kathleen; Chen, Zhongbo; Cheng, Jianguo
Abstract : Opioid tolerance (OT) and opioid‐induced hyperalgesia (OIH) are major challenges in medicine. Here we report that transplantation of mesenchymal stem cells (MSCs) prevented and reversed OT and OIH in rats and mice. The preventive and therapeutic effects were long‐lasting and consistent across different assessment schemes. Both intrathecal and intravenous transplantations were effective and safe. This emerging therapeutic strategy has thus shown promise to impact clinical practice and improve the efficacy and safety of opioid therapy.